Fracture behavior of directed energy deposition fabricated ph15-5 stainless steel - Lim, Jerron Yi Quan (Nanyang Technological University, 2022)
Direct energy deposition (DED) is one of the additive manufacturing (AM) technologies that have gained popularity mainly due to its potential for diversified processing activities such as repair of components, manufacturing for low volume of production and components with complex geometries. It would be useful in aerospace industries where parts are huge and direct repair on the components are feasible. Steels are the most used in many engineering sectors, and have tremendous interests in AM. Precipitation hardened (PH) stainless steels (SS) is infamous for their corrosion resistant, high strength and toughness used in engineering applications such as gears, valves, and turbine blades. However, there is limited research on the fatigue and fracture response of PH SS which plays an important role in applications with cyclic loading. This project discovers the effects of microcracks and flaws on the fatigue and fracture response of the PH15-5 SS. It was noted that the direction of microcracks with respect to the build orientation affects the mechanical characteristics of the material. The formation of microcracks could be due to solidification cracking that forms along the grain boundaries of the prior austenite phase. Upon conducting the fatigue crack growth and fracture toughness experiment, it was observed that the direction of microcrack parallel to the loading direction can act as a toughening mechanism due to crack arrest and crack blunting. This improves the toughness of the material despite noticing a drop in tensile strength when compared to conventionally manufactured PH SS. Whereas, the direction of microcracks perpendicular to the loading direction promotes an easier path for fatigue crack propagation. However, there are still crack deflection and crack blunting due to the orientation of microcracks, which is why it overall improves the toughness of the material. Other experiments such as tensile and hardness tests were performed to determine the mechanical properties. This project shows that microcracks can cause detrimental effect to the strength and hardness of the material, however, can be beneficial in toughening the material due to crack arrest and branching effect.